Pengaruh Kepemimpinan, Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) (Studi pada Tenaga Perawat pada RSUD dr. Haulussy Ambon) - Sahertian, Olivia Laura; Setiawan, Margono; Novadjaja, Lily Hendrasti (Jurnal Aplikasi Manajemen, 2011)
Successfulness and continuance of hospital it is very determined by organization member behavior. Practically, wrong behavior by organization member is an extra role behavior. This extra role behavior can increase organization performance by efficiency and effective in organization practice. Good quality of leadership, fulfilling job satisfaction and high commitment of organization from organization member can create good behavior. This research purpose is to analyze leadership influence, job satisfaction and organizational commitment towards Organizational Citizenship Behavior/OCB. The research conduct in RSUD dr. Haulussy Ambon, especially to nurse, the sample consist of 174 people as respondent. Data collected by questionnaire, interview and documentation, next the data in manner by using descriptive analysis and path analysis. The analysis result show that leadership have significant influence and positive towards OCB, job satisfaction have positive influenced towards OCB and organizational commitment have positive influence towards OCB. The analyze result either proving that leadership have indirect influence and positive towards OCB by job satisfaction, and also leadership have indirect influence and positive towards OCB by organizational commitment. In generally, organizational commitment gives biggest influence towards OCB.